Property, control and room for manoeuvre: Royal Dutch Shell and Nazi Germany, 1933–1945. Issue 3 (2nd April 2020) - Boon, Marten; Wubs, Ben
Abstract: Nationalistic Nazi politics created huge problems for foreign multinational firms in Germany. Business during the Nazi period has been characterised as either state controlled, complacent or complicit. Yet, some cases show that local management had considerable room for manoeuvre and acted primarily with the integrity and long-term interest of the company in mind. This article questions to what extent Royal Dutch Shell (RDS) controlled its assets in Nazi Germany and what its room for manoeuvre was. Although RDS lost control over its subsidiary over the course of the 1930s, the local management retained considerable room for manoeuvre well into the war.